Analisis Penghitungan Anggaran Belanja Daerah Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kota Medan Menggunakan Metode Activity Based Costing (ABC) - Fazri Aslam; Abriadi Rangkuti; Arini Arini; Rika Ramadhani; Fibri Rakhmawati (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
The Regional Revenue and Expenditure Budget (APBD), is the annual financial plan of regional governments in Indonesia which is approved by the Regional People's Representative Council. The APBD is determined by Regional Regulations and the APBD Fiscal Year covers a period of one year, starting from January 1 to December 31. This research aims to determine the grouping of activities from highest to lowest using the Activity Based Costing (ABC) method calculation. The research results show two analyzes, namely analysis in the sub-activities section and analysis in the operations expenditure section. The data used is Quantitative Data, which is data in the form of numbers or nominal data, data in the form of the Medan City BAPPEDA Budget Realization Report . Qualitative data is data that is not in the form of numbers or nominal, data in the form of direct observations from BAPPEDA Medan City regarding the implementation of the APBD. Data obtained from PERWAL APBD 2022 BAPPEDA Section is the total budget amount of Rp. 27,307,689,269 with 3 general activities, 12 sub-activities and 48 total operational expenditures.